2019
DOI: 10.3390/biom9040120
|View full text |Cite
|
Sign up to set email alerts
|

Combining Autoclaving with Mild Alkaline Solution as a Pretreatment Technique to Enhance Glucose Recovery from the Invasive Weed Chloris barbata

Abstract: Developing an optimum pretreatment condition to enhance glucose recovery assessed the potential of Chloris barbata, which is a common invasive weed in Thailand, as a feedstock for bioethanol production. Chloris barbata was exposed to autoclave-assisted alkaline pretreatment by using different sodium hydroxide (NaOH) concentrations (1% to 4%) and heat intensities (110 °C to 130 °C) that were dissipated from autoclaving. The optimum condition for pretreatment was determined to be 2% NaOH at 110 °C for 60 min. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Pretreatment using DW did not significantly affect the complex structure of CNS and SR decreased to 54.5%. Obeng et al reported that low SR disrupts the sugar recovery from biomass during enzymatic hydrolysis [ 25 ]. These results indicate that pretreatment using DW was not suitable for CNS pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment using DW did not significantly affect the complex structure of CNS and SR decreased to 54.5%. Obeng et al reported that low SR disrupts the sugar recovery from biomass during enzymatic hydrolysis [ 25 ]. These results indicate that pretreatment using DW was not suitable for CNS pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Collection and processing of durian peel were carried out as previously described in Obeng, Premjet & Premjet (2019) . Monthong and chanee peels (refer to Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The structural carbohydrates and lignin ( Sluiter et al, 2012 ) contents of durian peel were analyzed according to the National Renewable Energy Laboratory (NREL, Golden, CO, USA) analytical procedures. The contents of monosaccharides were determined as described in Obeng, Premjet & Premjet (2019) using the high-performance liquid chromatography (HPLC) system (Agilent 1100, Agilent Technologies, Waldbronn, Germany). The HPLC system consisted of a G1362A (Agilent Technologies, Waldbronn, Germany) refractive index detector (RID) and Bio-Rad Aminex HPX-87P column (Bio-Rad Laboratories, Inc., Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…At NaOH concentrations of 2% or more, SR decreased below 40%. In the sugar conversion process from biomass, sugar recovery is hindered by low SR [42]. Severe pretreatment conditions such as high temperature and solvent concentration, and long reaction time lead to low SR [43].…”
Section: Effect Of Naoh Pretreatment On Carbohydrate Composition Of Sicyos Angulatusmentioning
confidence: 99%